Low host immune pressure may be associated with the development of hepatocellular carcinoma: a longitudinal analysis of complete genomes of the HBV 1762T, 1764A mutant - Jiang, Zhi-Hua; Chen, Qin-Yan; Jia, Hui-Hua; Wang, Xue-Yan; Zhang, Lu-Juan; Huang, Xiao-Qian; Harrison, Tim J.; Jackson, J. Brooks; Wu, Li; Fang, Zhong-Liao (Frontiers in Oncology, 2023)
Background: It has been reported that hepatitis B virus (HBV) double mutations (A1762T, G1764A) are an aetiological factor of hepatocellular carcinoma (HCC). However, it is unclear who is prone to develop HCC, among those infected with the mutant. Exploring HBV quasispecies, which are strongly influenced by host immune pressure, may provide more information about the association of viral factors and HCC.Materials and methods: Nine HCC cases and 10 controls were selected from the Long An cohort.Serum samples were collected in 2004 and 2019 from subjects with HBV double mutations and the complete genome of HBV was amplified and sequenced using next-generation sequencing (NGS).The Shannon entropy values increased from 2004 to 2019 in most cases and controls. There was no significant difference in mean intrahost quasispecies genetic distances between cases and controls. The change in the values of mean intrahost quasispecies genetic distances of the controls between 2004 and 2019 was significantly higher than that of the cases (P<0.05). The viral loads did not differ significantly between cases and controls in 2004(p=0.086) but differed at diagnosed in 2019 (p=0.009). Three mutations occurring with increasing frequency from 2004 to 2019 were identified in the HCC cases, including nt446 C→G, nt514 A→C and nt2857T→C. Their frequency differed significantly between the cases and controls (P<0.05).The change in the values of mean intrahost quasispecies genetic distances in HCC was smaller, suggesting that HBV in HCC cases may be subject to low host immune pressure. Increasing viral loads during long-term infection are associated with the development of HCC. The novel mutations may increase the risk for HCC.